Récits de guerre et autres conflits chez Claude Barsotti, entre fiction et témoignage - Marie-Jeanne Verny (Lengas)
Claudi Barsotti, a La Marseillaise columnist for a long time and with a passion for research, is also the author of four narratives La Tèrra deis autres (1979), Testimòni d'un niston de la guèrra, autobiografia (2002), Lo comunard de la Mitidjà (2006) Lo Capitani de la Republica (2012) situated between fiction writing and personal account. Their analysis reveals that beyond an assumed subjectivity and throughout his whole work, Barsotti has had the objective of revitalising the remembrance of those who died forgotten by all.